Assessment of climatic change impacts on coastal zones in the Mediterranean: UNEP's vulnerability assessments methodology and evidence from case studies - Dimitrios Georgas (Fondazione Eni Enrico Mattei (FEEM), 2000)
The paper presents part of the overall United Nations Environment Programme Mediterranean work on the Implications of Future Climatic Changes for the Mediterranean Coastal Region. Most of this was published in Climatic Changes and the Mediterranean; Environmental and societal impacts of climatic change and sea level rise in the Mediterranean region, Vol 2, 1996. It compares the main findings, conclusions and recommendations of the regional and 11 site-specific studies in the Mediterranean, undertaken: a) to assess the likely implications of predicted climatic change on the natural and man-made environment and activities; b) to identify areas and systems most vulnerable to the expected change; and c) to suggest policies and measures that may avoid or reduce the negative impact of predicted change or adapt to such change. The evaluation of the methodology used in the preparation of site-specific studies is described and analysed in detail, and the impact of the studies on national, regional and local development policies and plans is assessed.
Keywords: 330; Mediterranean; UNEP; greenhouse effect; climatic changes; sea level changes; coastal; implications; climatic scenario; impacts; Klimawandel; Umweltbewertung; Küstenregion; Mittelmeerraum